2021
DOI: 10.1055/s-0041-1730960
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postinfection Hearing with Audiological Tests in Patients with COVID-19: A Case–Control Study

Abstract: Background Some viral infections can cause congenital or acquired unilateral or bilateral hearing loss. It is predicted that the coronavirus disease 2019 (COVID-19) virus, which can affect many systems in the body, may also have a negative effect on hearing. Purpose This study evaluated the effects of COVID-19 infection on pure-tone average. Research Design A case–control study. Materials and Methods A total of 104 volunteers (48 control, 56 experimental group) who applied to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The reported rate of otological or vestibular symptoms varied significantly. For example, Korkmaz et al (2021) Ricciardiello et al (2021) reported that both ears can equally be affected, and the impairment could be unilateral or bilateral, and if bilateral, the symptoms can be symmetrical or nonsymmetrical (Karimi-Galougahi et al, 2020;Koparal & Yılmazer, 2021;Koumpa et al, 2020;Sriwijitalai & Wiwanitkit, 2020), with the severity of the hearing loss documented to range from mild loss to profound hearing loss (Beckers et al, 2021;Chern et al, 2021;Koparal & Yılmazer, 2021;Koumpa et al, 2020;Pokharel et al, 2021) and some evidence of puretone average being substantially worse in patients with COVID-19 when compared with healthy control groups, particularly in the high frequencies (Koparal & Yılmazer, 2021). Mustafa (2020) found that pure-tone hearing thresholds in high frequencies and amplitudes of transient evoked otoacoustic emissions (TEOAE) were significantly worse in this population, thus concluding that COVID-19 infection potentially has adverse effects on cochlear hair cell function even when infected individuals are asymptomatic for the cardinal disease symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reported rate of otological or vestibular symptoms varied significantly. For example, Korkmaz et al (2021) Ricciardiello et al (2021) reported that both ears can equally be affected, and the impairment could be unilateral or bilateral, and if bilateral, the symptoms can be symmetrical or nonsymmetrical (Karimi-Galougahi et al, 2020;Koparal & Yılmazer, 2021;Koumpa et al, 2020;Sriwijitalai & Wiwanitkit, 2020), with the severity of the hearing loss documented to range from mild loss to profound hearing loss (Beckers et al, 2021;Chern et al, 2021;Koparal & Yılmazer, 2021;Koumpa et al, 2020;Pokharel et al, 2021) and some evidence of puretone average being substantially worse in patients with COVID-19 when compared with healthy control groups, particularly in the high frequencies (Koparal & Yılmazer, 2021). Mustafa (2020) found that pure-tone hearing thresholds in high frequencies and amplitudes of transient evoked otoacoustic emissions (TEOAE) were significantly worse in this population, thus concluding that COVID-19 infection potentially has adverse effects on cochlear hair cell function even when infected individuals are asymptomatic for the cardinal disease symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, notwithstanding this research quality challenge, the limited evidence that exists seems to warrant the need for careful audiological assessment and monitoring and polymerase chain reaction (PCR) testing for COVID-19 diagnosis in patients with sudden unexplained cochleovestibular features during COVID-19 (Beckers et al, 2021 ; Jafari et al, 2021 ; Koparal & Yılmazer, 2021 ) and children born to mothers who were COVID-19 positive during pregnancy (Alan & Alan, 2021 ; Oskovi-Kaplan et al, 2022 ; Yıldız et al, 2021 ). This is particularly important as definitive evidence is required to ensure that appropriate treatment is provided that takes into cognisance the therapeutic dilemmas surrounding the use of steroids in this population, as raised by Karimi-Galougahi et al ( 2020 ), the need for patient isolation and the possibilities of monitoring for late onset hearing loss in children born to mothers who were COVID-19 positive during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because there was no reason to assume that the virus would attack a specific ear and as previous studies have shown similar effects in both ears, 3 , 8 , 9 , 10 the results in the right and left ears of each participant were averaged. To answer our research questions, the air conduction thresholds were divided into three frequency ranges: low = 250–500 Hz, mid = 1000–3000 Hz, and high = 4000–8000 Hz.…”
Section: Methodsmentioning
confidence: 99%